Smart Liquefied Petroleum Gas (LPG) Leakage Detector using Internet of Things (IoT) - Jusshairi, Nur Erina Natasha (IRC, 2019)
Gas leakage is one of the factors that cause of fire in several places such as home, industries, canteen, etc. as this place using flammable gases such as Liquefied Petroleum Gas (LPG). In Malaysia, most of the LPG user are basically from the residential and commercial areas. Failure in detect any gas leakage in the early stage may lead to damage in life and properties. To overcome this situation, Smart Liquefied Petroleum Gas (LPG) Leakage Detector using Internet of Things (IoT) will help the issues to monitor and detect the gas leakage in real time and automatically close the gas cylinder valve once the leakage has occurred and detected. Besides, user will get alert and notification in case of any leakage detection via a buzzer and mobile notification.